SISTEM PENAMPIL INFORMASI KOLEKSI BATIK BERBASIS QR CODE DI GEDUNG SEMINAR SITI WALIDAH MUHAMMADIYAH SURAKARTA - Eri Prawira Kadarisman; Heru Supriyono (Jurnal Ilmiah SINUS, 2019)
The seminar room of Siti Walidah building is often visited by students or general public in which there are ancient batik collection displayed on its wall without any information about them. Smartphone technology has grown rapidly in which people can obtain information needed very easily. QR code is an easy method to get complete information. QR code is a type of image that stores data in the form of a barcode matrix in it. The purpose of this research is to make visitors get information about the displayed batik by using their smartphone. The method used in this study was the System Development Life Cycle (SDLC). The results obtained from this research were that the website admin systems managed batik information and the android application serves as information viewers of the batik collections that utilize the QR Code to be scanned. The testing carried out by the writer provided users with a comfortable experience to use the system and check whether it had worked correctly according to its function. The testing was done by testing the blackbox that made the results run well. In testing the QR code, the application scanned the image with sufficient lighting on ideal distance of 20cm to 40cm. On QR scribble tests, the code in the fifth streak could not be scanned.  For testing, smartphones with various specifications successfully ran the application and in testing the questionnaire, it produced an average accuracy of 88%. It is finally concluded that the application can help visitors to find out information about the batik displayed on the wall of the seminar room of Siti Walidah building, Muhammadiyah University of Surakarta.